The extent to which the students of the Arabic language departments have the ability to correct the linguistic errors prescribed in the Arabic language curricula for the secondary stage - Asst. Prof. Hussein Kareem Fozan (Journal of College of Education, 2024)
This research aims to build a remedial educational program in light of the Find the Error strategy to correct spelling errors among middle school students. To achieve that goal, the researcher followed a descriptive research approach. The research community was represented by middle school students, Arabic language teachers, male and female teachers, and specialized experts. As for the research sample, it was chosen from the statistical community for research. In a simple random method, it reached (60) male and female students. And (20) male and female teachers, and (10) arbitrators. Then the researcher prepared the research tool represented by building the remedial educational program and designing it according to the scientific steps. These steps were verified using the statistical methods used, and in light of the results reached by this study, the following can be concluded. :1- Preparatory stage students’ weak possession of spelling rules and many mistakes based on the results of a previous test presented to them.2-The content of the educational program and its activities are appropriate for treating spelling errors among middle school students
Keywords: Program, educational, therapeutic, find the error, dictation.